2017
DOI: 10.1177/0899764017692039
|View full text |Cite
|
Sign up to set email alerts
|

Improving Charity Accountability: Lessons From the Scottish Experience

Abstract: This paper examines the relevance and effectiveness of a charity accountability monitoring program in Scotland. The Scottish charity sector is vibrant and growing but the regulatory regime is in flux. Drawing upon a novel panel dataset of 21,322 observations on 5,124 organizations for the period 2007-2013, this study examines charity accountability from the perspective of the regulator and analyzes its attempts to encourage acceptable norms and practices in the sector. The results reveal that a majority of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…The literature does, however, raise concerns that various regulatory accountability developments seem to reflect a market-based view of the NPO environment, rather than one which delivers new accountabilities (Harrow, 2006;McDonnell, 2017;Morgan & Fletcher, 2013). For example Connolly, Hyndman, and McConville (2013b) explore the use of conversion ratios as a measure of efficiency.…”
Section: Studies Examining Regulatory Compliancementioning
confidence: 99%
“…The literature does, however, raise concerns that various regulatory accountability developments seem to reflect a market-based view of the NPO environment, rather than one which delivers new accountabilities (Harrow, 2006;McDonnell, 2017;Morgan & Fletcher, 2013). For example Connolly, Hyndman, and McConville (2013b) explore the use of conversion ratios as a measure of efficiency.…”
Section: Studies Examining Regulatory Compliancementioning
confidence: 99%
“…• Stricter enforcement increases regulatory complexity further and triggers the development of more complex non-profit structures (Kerlin & Reid, 2010) leading to accountability concerns (McDonnell, 2017).…”
Section: Enabler 34mentioning
confidence: 99%
“…Finally, regulation can be an expensive way of increasing public trust, with Bekkers (2003) finding no clear link between increased regulation and increased trust in charities. Similarly, McDonnell (2017), in a longitudinal study of Scottish charities, found no link between the presence of regulator‐defined accountability concerns (e.g., possible failure to apply funds for charitable purposes) and negative organizational outcomes such as dissolution or misconduct.…”
Section: Theorymentioning
confidence: 99%